2006
DOI: 10.1128/jvi.02746-05
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus Macaque Polyclonal and Monoclonal Antibodies Inhibit Simian Immunodeficiency Virus in the Presence of Human or Autologous Rhesus Effector Cells

Abstract: Although antibodies can prevent or modulate lentivirus infections in nonhuman primates, the biological functions of antibody responsible for such effects are not known. We sought to determine the role of antibodydependent cell-mediated virus inhibition (ADCVI), an antibody function that inhibits virus yield from infected cells in the presence of Fc receptor-bearing effector cells, in preventing or controlling SIVmac251 infection in rhesus macaques (Macaca mulatta). Using CEMx174 cells infected with simian immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
92
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 46 publications
4
92
0
Order By: Relevance
“…This discordance might be explained by the fact that the panel used for neutralizing assays did not include the strains used in our ADCVI assays. However, discordance between ADCVI or ADCC and neutralizing activities has been observed previously and may be due to differences in antigenic targets or in the subclass distribution of the two functional Ab responses (13,30,31). Alternatively, the Ag-Ab affinity required for ADCVI might be less than that required for neutralization because ADCVI Ab need not block virus-receptor interactions.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…This discordance might be explained by the fact that the panel used for neutralizing assays did not include the strains used in our ADCVI assays. However, discordance between ADCVI or ADCC and neutralizing activities has been observed previously and may be due to differences in antigenic targets or in the subclass distribution of the two functional Ab responses (13,30,31). Alternatively, the Ag-Ab affinity required for ADCVI might be less than that required for neutralization because ADCVI Ab need not block virus-receptor interactions.…”
Section: Discussionmentioning
confidence: 79%
“…One explanation for the discordance between ADCVI activity and the other Abs is our use of a clinical R5 strain of HIV-1 grown in PBMCs (46). Additionally, we and others (13,30,31) have shown that functional Ab responses directed against infected cells and requiring Fc-Fc␥R interactions do not necessarily correlate with neutralizing or binding Ab levels; our current results further underscore the fact that Ab functions are not necessarily predictable from binding assays and that assays used to measure one function might not predict another.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…By this process, antiviral antibodies bind to infected cells that are killed by NK cells and neutrophils. A protective role of ADCC, but not NAbs, has been reported in macaques that were vaccinated for SIV [74]. Still, a recent study suggests that HIV can also escape from ADCC [75].…”
Section: B Cells and Antibodiesmentioning
confidence: 99%